2020
DOI: 10.5713/ajas.18.0795
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional efficiency of feed restricted F1 Holstein/Zebu cows during the middle third of lactation

Abstract: The objective of this study was to evaluate the effects of different levels of quanti tative feed restriction on nutrient intake and digestibility, nitrogen balance, efficiency and feeding behavior, and productive performance in F1 Holstein/Zebu cows during the middle third of their lactation. Methods: Sixty F1 Holstein/Zebu cows with 111.5±11.75 days of lactation and an initial body weight (BW) of 499±30 kg (mean±standard error of the mean) were used. The experimental design was completely randomized with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The higher iNDF concentration (227.4 g/kg) in the EGPS diet implies less fibrous fraction degradability, which limited the TDN intake in this diet, indicating lower energy availability for rumen fermentation (Borges et al 2019). However, Monção et al (2020 and Santana et al (2019Santana et al ( , 2020 recommended DMI for F1 Holstein/Zebu cows in the order of 2.50% BW. In this study, although lower DMI was found in cows that received the EGSP and SCPS diet, the DMI is above 2.50% BW not impairing the performance of the animals as justified by milk yield that did not change between treatments.…”
Section: Animals Feed Intakementioning
confidence: 99%
See 1 more Smart Citation
“…The higher iNDF concentration (227.4 g/kg) in the EGPS diet implies less fibrous fraction degradability, which limited the TDN intake in this diet, indicating lower energy availability for rumen fermentation (Borges et al 2019). However, Monção et al (2020 and Santana et al (2019Santana et al ( , 2020 recommended DMI for F1 Holstein/Zebu cows in the order of 2.50% BW. In this study, although lower DMI was found in cows that received the EGSP and SCPS diet, the DMI is above 2.50% BW not impairing the performance of the animals as justified by milk yield that did not change between treatments.…”
Section: Animals Feed Intakementioning
confidence: 99%
“…In the semiarid region of Brazil, sorghum silage (Sorghum bicolour (L.) Moench) It is traditionally used as a roughage (fibre source) for feedlot dairy cows due to tolerance to water restriction, mechanisable and high productivity per unit area and good nutritional value (Borges et al 2019). However, the feed cost under these conditions is high (Borges et al 2019;Santana et al 2019Santana et al , 2020. The use of traditional ingredients or byproducts and/or agribusiness wastes available in each region in the formulation of diets is a strategy to reduce feed costs and improve system efficiency.…”
Section: Introductionmentioning
confidence: 99%